Characterization of Enteric Neurons in Wild-Type and Mutant Zebrafish Using Semi-Automated Cell Counting and Co-Expression Analysis - Simonson, Levi W. (Mary Ann Liebert, Inc., 2013)
To characterize fluorescent enteric neurons labeled for expression of cytoplasmic markers in zebrafish mutants, we developed a new MATLAB-based program that can be trained by user input. We used the program to count enteric neurons and to analyze co-expression of the neuronal marker, Elavl, and the neuronal subtype marker, serotonin, in 3D confocal image stacks of dissected whole-mount zebrafish intestines. We quantified the entire population of enteric neurons and the serotonergic subpopulation in specific regions of the intestines of gutwrencher mutant and wild-type sibling larvae. We show a marked decrease in enteric neurons in gutwrencher mutants that is more severe at the caudal end of the intestine. We also show that gutwrencher mutants have the same number of serotonin-positive enteroendocrine cells in the intestine as wild types.